EFEKTIVITAS PELATIHAN DAN INTERNSHIP OTC BALI UNTUK KOMPETENSI TENAGA KERJA PARIWISATA - Redyanti, PEP.; Sudiarta, I Nyoman; Sasrawan Mananda, IGPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024), 2025)
The growth of the tourism sector has led to an increase in demand for qualified and skilled labor. Vocational Education and Training Institutions (LPK) have a strategic role in building competent human resources. Overseas Training Center (OTC) Bali Gianyar International Tourism and Cruise Line College as a job training institution, especially in the field of tourism supports the government's efforts to improve the quality of human resources by providing a variety of job training programs in Bali. The purpose of this study is to evaluate the effectiveness of training and internship programs implemented by OTC Bali Gianyar as an effort to improve the competence of the workforce in the tourism sector and analyze the challenges faced by OTC Bali Gianyar in implementing the program. This research uses quantitative and qualitative methods (mix method) with concurrent embedded model, where quantitative and qualitative data are used simultaneously / together, but the weight of the method is different. Data were collected using questionnaire and interview techniques. Respondents in this study were 97 respondents who met the criteria as alumni of OTC Bali Gianyar. The data results were formulated and tested using Multiple Linear Regression Analysis. While qualitative analysis is taken from the interpretation of data by providing information and explanations. The results showed that training and internship programs have a high level of effectiveness in improving workforce competence.